PENGARUH SEKTOR PARIWISATA DAN RETRIBUSI DAERAH TERHADAP PAD DAN PENYERAPAN TENAGA KERJA KABUPATEN/KOTA PROVINSI BALI - Fernanda, I Putu Ricky Mahesa; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The tourism sector is industry always experiencing development, so that it can increase employment. The research objective (1) analyze influence of tourism sector and local fees on PAD districts / cities Bali Province. (2) analyze influence of tourism sector, regional levies and PAD on absorption of labor districts / cities Bali Province. (3) analyze PAD mediates influence of tourism sector, regional levies and local revenue in districts / cities Bali Province. The method used non-participant, with path analysis and secondary data. The results this study indicate the tourism sector has positive and insignificant effect on PAD in the Regency / City Bali Province, while the local levies don’t have significant positive effect on local income in Regency / City of Bali Province. The tourism sector and PAD have significant positive effect on employment in Regency / City of Bali Province, while the local levy no significant positive effect on labor absorption in the Regency / City Bali Province. PAD partially mediates the effect of local user fees on labor absorption, while PAD doesn’t partially mediate the influence of tourism sector on labor absorption in Regency / City Bali Province.   Keywords: Tourism Sector, Regional Retribution, Original Local Revenue, Labor Absorption